ANALISIS PENGARUH MINAT BELI ULANG PADA KONSUMEN NOKIA KOTA SEMARANG (Students' Journal of Economic and Management, 2013)
This research is purpose to find out whether the quality of product, perception of price, and attractiveness of advertising affect on consumer repurchase intention Nokia mobile phone products and analyzing the most dominant factor in influencing consumer’s repurchase intention on Nokia mobile phones in Semarang.The sampel size of this research is 100 with technique of sampling is purposive accidental sampling and 5% signification. This research used is qualitative and quantitative research with survey approach. Technique of data analysis that used are, validity and reliability from points of questioner,double liniar regress test, normality test, multikolinearitas test, heteroskedastisitas test, simultan (F test), determination coefficient and partially (t test).Using the statistical process social science (SPSS) for regress test. The result show that, product quality according to positive and significant influence repurchase intention are 0.405, attractiveness of advertising according to positive and significant influence repurchase intention are0.331 and perception of price according t positive and significant influence repurchase intention are 0.239. hypothesis testing by using test t that product quality, perception of price and attractiveness of advertising that canvassed, scond variabel according to positive an significant influence repurchase intention. While determination coefficientis got with value adjusted R2 76,8% means, repurchase intention variable explainable by existence variable of product quality, perception of price and attractiveness of advertising, while the rest 23,2% can be influced by other variable.Keywords : Product Quality, Perception Of Price, Attractiveness Of Advertising and Repurchase